Identification of new chickpea genotypes resistant to fusarium wilt (Fusarium oxysporum f. sp. ciceris) - Istanbuli, Tawffiq; Kemal, Seid Ahmed; Tawkaz, Sawsan; Hamwieh, Aladdin (The Arab Society for Plant Protection, 2022)
Fusarium wilt (Fusarium oxysporum f. sp. ciceris) of chickpea is the major limitation to chickpea production worldwide. Host plant resistance is the major component in the management of fungal diseases in chickpea. This study was conducted with the aim to find new sources of resistance chickpea genotypes against fusarium wilt. The experiment was conducted in 2017-2018 at the sick plot at the International Center of Agricultural Research in the Dry Area (ICARDA), Terbol station, Bekaa valley, Lebanon. The experiment was laid out in an augmented block design (ABD), and the high susceptible check (ILC482) was repeated after each tenth row. The total number of the genotypes used in this study was 974, they included (34) accessions from the genebank, and (940) breeding lines from the chickpea breeding program at the ICARDA. Finally, 45 promising lines without symptoms were selected to be distributed through the chickpea fusarium wilt Nursery (CFWN) in 2021 for further testing in different locations. This is an important material in chickpea to enhance fusarium wilt chickpea resistance in the future.